Aura child : the incredible story of a special gift - Kaymen, A. I. (Andrews UK, 2013)
This is one of the most astonishing books you will ever read, the story of a very special child. Everybody has a gift, but some are more special than others. And perhaps some are more of a curse than a blessing. Imagine growing up seeing the world in a completely different way to everyone you know, in a way that nobody - even your own family - can understand or will even acknowledge ... You can see every person's energy field around them, and you can see how it changes as they speak, as they ...